(untitled) (Hà Nội, 2000)
Viết về cuộc chiến tranh vệ quốc vĩ đại của dân tộc việt Nam từ 1858 - 1975
Keywords: America,French,Vietnam,Vietnam,Vietnam,Vietnamese conflict; Colonies,Colonies,History,History,War; 1945-1975,1970-1975,1970-1975,1960 - 1975